Epidemiology of genital Chlamydia trachomatis in England and Wales. Issue 2 (April 1997) - Simms, I; Catchpole, M; Brugha, R; Rogers, P; Mallinson, H; Nicoll, A
Abstract : OBJECTIVE: To describe the recent epidemiology of genital Chlamydia trachomatis infection in England and Wales. DESIGN: Retrospective study of routinely available surveillance datasets and ad hoc prevalence studies. METHODS: Numbers of new cases of genital C trachomatis infection, obtained from the Department of Health and Welsh Office, were combined with the estimated mid-year resident population of England and Wales. Rates were analysed for trend over time using a log linear age period model in GLIM4. Ad hoc prevalence and case finding studies carried out over the past 20 years were critically assessed in terms of study design and testing methodologies. RESULTS: Attendance rates at genitourinary medicine (GUM) clinics were higher for women than men over the period 1989 to 1994 as were the number of laboratory reports. The highest rate of attendance (GUM clinic data) was for women aged 16 to 19 years. There was an overall significant linear decrease in the attendance rates over time for both men (p = 0.0172) and women (p = 0.0000) between 1989 and 1994. There was considerable variation in the prevalence of genital C trachomatis infection detected within different clinical settings, together with a substantial level of asymptomatic infection. CONCLUSIONS: Genital C trachomatis infection is broadly distributed throughout the sexually active population, with a substantial reservoir of asymptomatic infection among those generally perceived to be at low risk of a sexually transmitted infection. Young people, particularly women aged 16 to 19 years, are at highest risk of genital C trachomatis infection. This is of concern since younger women are more susceptible than older women to developing complications of chlamydial infection, such as pelvic inflammatory disease. The broad distribution of infection across all sexually active health service attenders and the high level of asymptomatic infection suggest that a new, screening based, approach to the control of genital C trachomatis infection is required. Recommendations are made as to the epidemiological research required to guide such work.